Socioeconomic and Environmental valuation of the Ecosystem Services: A Case Study of from Zoobotonical Park in Belém, Pará, Brazil - Santana, Antônio Cordeiro de; Santana, Ádina Lima de; da Silva de Oliveira, Gilmara Maureline Teles; Salomão, Rafael de Paiva; Santana, Ádamo Lima de; Oliveira, Eder Silva de; Savaris dos Santos, Washington Aleksander (International Journal of Advanced Engineering Research and Science, 2022)
The value of ecosystem services produced by the natural ecosystem preserved by the Zoobotanical Park of Belém (ZPB) was estimated based on the population's perception of the existing link between nature and the well-being that is provided to society. The preserved ecosystem provides the population with physical and mental benefits through individual and collective recreation, contemplation of the environment and direct and indirect interaction with animals and plants, as well as knowledge about endangered species and awareness of the need to preserve natural resources in the Amazon. The wood products were estimated by the Net Present Value (NPV), considering a flow of 100 years, as proposed by the Brazilian Institute of Environment and Renewable Natural Resources (IBAMA). Three methods of estimating the NPV were adopted: the value of the carbon stock evolving based on the geometric rate of growth of the diameter of the trees, which resulted in the value of (US 145,216.75); the value of the carbon stock without growth rate, with a value of (US 66,332.21); and the value of the wood volume of (US 34,660.36). The value of ecosystem services was estimated by the Integrated Method of Contingent Valuation and generated the socioeconomic and environmental value for preserving the ZPB of US 1,464,527.41 and the value of replacing it with another activity at US 1,628,657.59. This amount was more than twice the opportunity cost of the park area for the civil construction market.